(untitled) (Itinera, 2024)
In this essay I compare the landscape philosophy proposed by Joachim Ritter in his famous essay Landschaft (1963) and the landscape theory elaborated by French geographer and orientalist Augustin Berque, focussing primarily on the volume La pensée paysagère (2008). The perspective from which the comparison is advanced concerns the problem of aesthetic appraisal and experience and its relation to the geographical reality to which landscape refers. The confrontation between Ritter and Berque brings the tradition of philosophical aesthetics into confrontation with that of human geography, as part of a path aimed progressively at overcoming the separation of the aesthetic (of which the aestheticized concept of landscape typical of the tradition of Western art history would be an expression) from the other spheres of meaning with which space is invested, from the ecological- environmental to the ethical-political.